Computer-assisted and robotic endoscopy : third International Workshop, CARE 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Revised selected papers /: third International Workshop, CARE 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Revised selected papers. (2017) - Unknown
No abstract available